Comparison of underwater with conventional pumped hydro-energy storage systems - Dubbers, Dirk (Journal of energy storage, 2021)
The laws of fluid mechanics imply that modular offshore pumped hydro-energy storage systems like StEnSEA have no advantage over similar but much cheaper modular onshore systems.
Gesehen am 04.05.2021